Effect of Different Media on Growth of Cauliflower Seedling - Timalsina, Manoj (Nepalese Journal of Agricultural Sciences, 2026)
The growing medium plays a significant role in the quality and performance of vegetable seedlings. Therefore, this study was undertaken to investigate the effect of media on the growth of cauliflower (Brassica oleracea var. botrytis) seedlings. The experiment was conducted inside a plastic house at the Spices Crop Development Center (SCDC), Panchkhal, Kavrepalanchowk, Nepal, from August to September 2020. The seven media types used in this study include pure cocopeat, peatmoss, vermicompost, and soil, cocopeat plus peatmoss (1:1 by volume), cocopeat plus vermicompost (1:1 by volume), and soil plus compost (1:1 by volume). The experiment was conducted under RCBD with seven treatments and three replications. Data on germination percentage, number of leaves, shoot length, shoot diameter, shoot fresh weight, root length, and root fresh weight were recorded and analyzed using ANOVA in RStudio. Results indicated that there were significant differences among media for the germination percentage, shoot diameter, and shoot fresh weight at p ≤ 0.05. Maximum germination of 75.25% was observed in cocopeat, which also produced the best overall growth performance, followed by a combination of cocopeat plus vermicompost and cocopeat plus peatmoss, while soil and peatmoss proved to be poor. The study concludes that cocopeat-based media enhance growth and quality in cauliflower seedlings and can be recommended for commercial nursery practices in Nepal.